Biometrics and gas exchange of ornamental palm trees in different sources of fertilization (Research, Society and Development, 2021)
Aiming to analyze the biometric characteristics and gas exchange patterns in the development of Veitchia merrillii (Becc.), HE Moore, under the effect of different fertilizer sources, an experiment was conducted in a controlled environment, using randomized blocks as an experimental design, composed of 13 treatments, with different doses of NPK, commercial biofertilizer and homemade biofertilizer. Height, stem diameter and number of leaves were measured at 30, 60, 90 and 120 days after transplanting (DAT), and gas exchange analysis was performed at 30 DAT. Regression analysis was performed to determine the response doses of each fertilizer. The recommended dose for the chemical fertilizer is 10.5 g, of commercial biofertilizer 150 ml. L -1, the ideal dose of homemade biofertilizer was linear. The treatments, with the exception of the control, showed high values of photosynthesis and low values for transpiration, indicating excellent conditions for the field. The treatment that was most successful in terms of aesthetic characteristics was the T7 treatment.